The Female Figure in Contemporary Historical Fiction
XIII, 241 p.
Keywords: From The Other Boleyn Girl to Fingersmith , this collection explores the popularity of female-centred historical novels in recent years. It asks how these representations are influenced by contemporary gender politics, and whether they can be seen as part of a wider feminist project to recover women's history.